Structural basis of protein kinase C and the interactions with modulators - Nuttee Suree (2018)
© 2018 Nova Science Publishers, Inc. Protein kinase C (PKC) isozymes have been implicated in many diseases and thus become of great interest for their therapeutic potential. However, structural details in the binding mechanism to their modulators and the specific pathways by which they undertake to trigger cellular localization are still largely unclear. Moreover, despite many efforts have been put on describing comprehensive structural details, either of the free protein or the activator-bound form, dynamics information of the structures is still lacking, thus hampering the development of potential therapeutic modulatory compounds. In this chapter, we will review the structural basis of PKC isozymes and focus on the C1 domain, as well as the plausible binding mechanisms of its activators. The recent molecular dynamics simulation studies of how phorbol esters or bryostatin bind to the activator pocket will be described in order to gain insights into the binding. Finally, some of the key amino acid residues recently identified as important for the activator binding will be investigated, which will shed light onto ways to develop potential therapeutic agents to target specifically to this class of enzymes.